Long-term oral exposure to safe dose of bisphenol A in association with high-fat diet stimulate the prostatic lesions in a rodent model for prostate cancer - Facina, Camila H. [UNESP]; Campos, Silvana G.P. [UNESP]; Gonçalves, Bianca F. [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Wiley, 2018)
Background: Studies have shown that exposure to environmental chemicals known as endocrine disruptors can cause permanent changes in genital organs, such as the prostate. Among these environmental chemicals stands out bisphenol A (BPA). Another factor associated with prostate changes is the consumption of a high-fat diet. Although the relationship between the consumption of a high-fat diet and an increased risk of prostate cancer is well established, the mechanisms that lead to the establishment of this disease are not completely understood, nor the simultaneous action of BPA and high-fat diet. Methods: Adult gerbils (100 days old) were divided in four groups (n = 6 per group): Control (C): animals that received a control diet and filtered water; Diet (D): animals that received a high-fat diet and filtered water; BPA: animals that received a control diet and BPA − 50 µg kg−1 day−1 in drinking water; BPA + Diet (BPA + D): animals that received a high-fat diet + BPA − 50 µg kg−1 day−1 in drinking water. After the experimental period (6 months), the dorsolateral and ventral prostate lobes were removed, and analyzed by several methods. Results: Histological analysis indicated premalignant and malignant lesions in both prostatic lobes. However, animals of the D, BPA, and BPA + D groups showed a higher incidence and larger number of prostatic lesions; inflammatory foci were also common. Markers to assess prostate lesions, such as increased activation of the DNA repair system (PCNA-positive cells), androgen receptor (AR), and number of basal cells, confirmed the histology. However, serum levels of testosterone did not change under the experimental conditions. Conclusions: The results indicated that the methodology used was effective in generating metabolic changes, which directly compromised prostatic homeostasis. Diet and BPA appear to modulate the activation of the AR pathway and thereby optimize tumor establishment in the gerbil prostate.
Keywords: androgen receptors; bisphenol A; high-fat diet; prostatic lesions; α-actin